Safety and efficacy of a feed additive consisting of locust bean gum for all animal species (Dupont Nutrition and Health). (5th August 2022) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Durjava, Mojca Fašmon; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel) was asked to deliver a scientific opinion on the safety and efficacy of locust bean gum as a technological feed additive (functional group: emulsifiers, gelling agents, stabilisers and thickeners) for all animal species. Owing the lack of sufficient data, no conclusions could be drawn on the safety of the additive for the target species or the user. The use of locust bean gum in animal nutrition under the proposed conditions of use is of no concern for consumer safety and the environment. The Panel concluded that the additive has potential to be efficacious as gelling agent, thickener and contributes to stabilise canned pet feed when used in synergy with another hydrocolloid (carrageenan). In the absence of data, the Panel could not conclude on the efficacy of the locust bean gum as an emulsifier.